Associations of plasma atrial natriuretic peptide and electrolyte levels with essential hypertension - HU, GUANGMEI (D.A. Spandidos, 2013)
This study aimed to investigate the associations among the levels of plasma atrial natriuretic peptide (ANP) and electrolytes and essential hypertension (EH) in Uygur, Han and Kazakh populations in Xinjiang. A total of 724 hypertensive participants of different ethnicities from Xinjiang (208 Uygur, 287 Han and 229 Kazakh) and 741 normal controls (208 Uygur, 267 Han and 266 Kazakh) were enrolled. The associations of ANP with serum potassium, serum sodium and blood pressure were assessed. In the normal control (NT) group, the concentration of ANP was higher in the Uygur population than in the Han population, and the concentration in the Han population was higher than that in the Kazakh population (P<0.05). In the EH group, the serum potassium levels of the Uygur and Han populations were higher than that of the Kazakh population (P<0.05). The ANP concentration in the Uygur ethnic group was higher than that in the Han population, which was in turn higher than that in the Kazakh participants (P<0.05). In the Kazakh population, the serum potassium level was significantly lower in the EH group compared with that in the NT group (P<0.05). The serum potassium level was significantly lower and the ANP concentration significantly higher in the EH group compared with those of NT groups in the Uygur and Han populations (P<0.05). Age and body mass index (BMI) were associated with hypertension in the Uygur, Han and Kazakh populations. Low serum potassium may be a risk factor of hypertension in individuals of Uygur and Kazakh ethnicity. Plasma ANP may be a regulatory factor involved in the development of hypertension in Uygur and Han populations.